Studi Kasus Motivasi Belajar Siswa SDS Unwanus Saadah - Nabilah, Firyal Yasmin; Rakhmania, Raisa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Learning motivation is the overall driving force within student that intiates learning activities, ensures the continuity of these activities, and provides direction to learning activities so that the objectives desired by the subject can be achieved. In elementary school, learning motivation becomes an important factor influencing students’ academic success and personal development. This study aims to identify the factors that influence the learning motivation of fourth grade students at SDS Unwanus Saadah. This study uses a qualitative case study approach. This approach allows the researcher to gain an in-depth understanding of the issues being studied through various data collection techniques, including structured interviews and FGD. The number of students involved in this study was six students. The collected data were then reduced through a coding process and conclusions were drawn to identify key themes. The results showed that both intrinsic factors and extrinsic factors influence students’ learning motivation, both positively and negatively. This study is expected to provide deeper insights into the factors that affect students’ learning motivation and offer suggestions for the development of more motivating pedagogical strategies and school environment.